Sustainable Healthcare Models in Developing Countries: Bridging Gaps in Universal Health Coverage - Meyka Aris Yusron; Faisal Razak; Zain Nizam (Yayasan Adra Karima Hubbi, 2025)
Coverage in developing countries, where persistent inequalities, financial constraints, and institutional fragmentation continue to limit access to essential health services. This study aims to examine how sustainable healthcare models contribute to bridging gaps in Universal Health Coverage by analyzing the interaction between financing mechanisms, governance structures, and service delivery systems. A qualitative comparative research design was employed, integrating secondary statistical data analysis, policy document review, and a case study approach to explore healthcare sustainability across selected developing countries. The findings reveal that healthcare systems characterized by stable public financing, reduced reliance on out-of-pocket payments, strong governance coordination, and a primary healthcare orientation demonstrate higher resilience and more equitable coverage outcomes. The results also indicate that fragmented policies, weak institutional capacity, and curative-centered investment patterns undermine long-term Universal Health Coverage efforts. The study concludes that embedding sustainability principles into healthcare models is critical for ensuring that coverage expansion is both inclusive and enduring. The novelty of this research lies in its integrative framework that conceptualizes sustainability as a systemic and relational process rather than a standalone policy objective, offering strategic insights for policymakers seeking to advance resilient and equitable Universal Health Coverage in developing countries.